Microvascular basis for growth of small infarcts following occlusion of single penetrating arterioles in mouse cortex. Issue 8 (August 2016) - Taylor, Zachary J; Hui, Edward S; Watson, Ashley N; Nie, Xingju; Deardorff, Rachael L; Jensen, Jens H; Helpern, Joseph A; Shih, Andy Y
Small cerebral infarcts, i.e. microinfarcts, are common in the aging brain and linked to vascular cognitive impairment. However, little is known about the acute growth of these minute lesions and their effect on blood flow in surrounding tissues. We modeled microinfarcts in the mouse cortex by inducing photothrombotic clots in single penetrating arterioles. The resultant hemodynamic changes in tissues surrounding the occluded vessel were then studied using in vivo two-photon microscopy. We were able to generate a spectrum of infarct volumes by occluding arterioles that carried a range of blood fluxes. Those resulting from occlusion of high-flux penetrating arterioles (flux of 2 nL/s or higher) exhibited a radial outgrowth that encompassed unusually large tissue volumes. The gradual expansion of these infarcts was propagated by an evolving insufficiency in capillary flow that encroached on territories of neighboring penetrating arterioles, leading to the stagnation and recruitment of their perfusion domains into the final infarct volume. Our results suggest that local collapse of microvascular function contributes to tissue damage incurred by single penetrating arteriole occlusions in mice, and that a similar mechanism may add to pathophysiology induced by microinfarcts of the human brain.